Challenges and prospects in mentoring medical scientists in Latin America: a narrative review and recommendations - Rodrigo C. Menezes; Rodrigo C. Menezes; Rodrigo C. Menezes; Caian L. Vinhaes; Caian L. Vinhaes; Caian L. Vinhaes; Caian L. Vinhaes; Felipe Ridolfi; Felipe Ridolfi; Isabella B. B. Ferreira; Isabella B. B. Ferreira; Isabella B. B. Ferreira; et al. (Frontiers in Medicine)
ObjectiveTo identify the challenges for the development and mentorship of physician-scientists in Latin America, outline the key barriers to integrating research training into medical education and post-graduate pathways, and propose recommendations to foster structured mentorship, improve institutional support, and strengthen the research ecosystem for future physician-scientists.Study designNarrative review.MethodsA narrative review of relevant literature, institutional reports, and existing educational models was undertaken. The authors synthesized information on current educational pathways, funding opportunities, institutional infrastructures, and mentorship practices for physician-scientists in Latin America and derived practical recommendations for improving mentorship and training structures.ResultsLatin America’s aspiring physician-scientists face fragmented educational programs, limited or inconsistent research integration in medical curricula, and inadequate mentorship support. These issues are exacerbated by overburdened healthcare systems, insufficient funding, low stipends, and a scarcity of dual-degree training programs. Institutional and funding barriers frequently force trainees and established researchers to choose between clinical practice and research, stifling the growth of a skilled physician-scientist workforce. Proposed solutions include developing integrated dual-degree and research residency programs, reforming medical curricula to include foundational research skills, strengthening mentorship networks through structured support and incentives, increasing research fellowship funding and removing exclusivity clauses, and creating regional consortia to standardize training and foster cross-border collaboration.ConclusionAddressing the systemic barriers to mentoring and training physician-scientists in Latin America is essential for building a robust, research-oriented medical community. The recommended structural reforms, with increasing funding, enhanced mentorship frameworks, and promoting regional partnerships, can help Latin America cultivate a sustainable environment for the development of physician-scientists.